Kufa: From a Military Encampment to a Significant City. A Study of Its Political and Social Conditions from Its Founding to the End of the Rashidun Caliphate. (17 AH - 41 AH)(648 -661 CE) (Journal of Human Sciences, 2025)
This study addresses the steps involved in the establishment of Kufa and the reasons for undertaking this process. It presents an analysis of its demographic composition and the changes that occurred within it, culminating in its transformation from merely a gathering of soldiers into a prominent political center in the Islamic state. The study highlights the most notable governors and judges in Kufa, taking care to avoid delving into the political and sectarian conflicts the city witnessed. The temporal framework of the study spans from its founding in the year 17 AH until the end of the Rashidun Caliphate in the year 40 AH.